Quality of life of diabetic patients of the land «Karaganda» depending of social and demographic factors - Turgunova, L.G.; Turmuchambetova, A.A.; Amirchanova, D.T.; Alina, A.R. (Fundamental and Experimental Biology, 2016)
Authors studied indicators of quality of life of patients with 2 type of diabetes depending on a risk of diabetes, socialand demographic factors among population of the Karaganda region. The research carried out according Sscientific program «Environmental Risks and Health of the Population». Screening included using of elaborated by authors of questionnaire contained official consent of respondent (patient) as information abouta sex, age, data on social factors (level of the income, family status (married or not), education, employment, nature of work), availability or absence of chronic diseases were specified. For determination of risk groups of diabetes the questionnaire of FINDRISC (The Finnish Diabetes Risk Score) was used. For a quality of life estimation the short version of questionnaire of WHO (WHOQOL-BREF) which consists of 26 questions. The analysis of results of a scale of FINDRISC showed that at 24.6 % of respondents in the next 10 years moderate, high and very high risk of SD took place (12 points and more).